2012
DOI: 10.4155/fmc.12.80
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors In The Treatment Of Cancer: Overview And Perspectives

Abstract: Histone deacetylase inhibitors (HDACis) are one of the last frontiers in pharmaceutical research. Several classes of HDACi have been identified. Although more than 20 HDACi are under preclinical and clinical investigation as single agents and in combination therapies against different cancers, just two of them were approved by the US FDA: Zolinza(®) and Istodax(®), both licensed for the treatment of cutaneous T-cell lymphoma, the latter also of peripheral T-cell lymphoma. Since HDAC enzymes act by forming mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
129
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 143 publications
0
129
1
1
Order By: Relevance
“…61,62 Using the knockdown approach, the highthroughput screening of HDAC showed that the class II HDACs, HDAC4 and HDAC9, regulate SMARCA2 expression. [61][62][63][64] We examined whether SMARCA2 expression was affected in SCC-11 cells and SCC-11M cells exposed to control media and 10 μg/ml cisplatin for 16 h (Fig. 4).…”
Section: Modulation Of Histone Deacetylation Affects the Smarca2 Exprmentioning
confidence: 99%
“…61,62 Using the knockdown approach, the highthroughput screening of HDAC showed that the class II HDACs, HDAC4 and HDAC9, regulate SMARCA2 expression. [61][62][63][64] We examined whether SMARCA2 expression was affected in SCC-11 cells and SCC-11M cells exposed to control media and 10 μg/ml cisplatin for 16 h (Fig. 4).…”
Section: Modulation Of Histone Deacetylation Affects the Smarca2 Exprmentioning
confidence: 99%
“…Combination of sorafenib with chloroquine significantly suppressed tumor growth compared with sorafenib alone [45, 47]. Vorinostat is the first histone deacetylases (HDAC) inhibitor to be approved for human clinical use [92]. Vorinostat can sensitize HCC cells to sorafenib treatment by regulating the acetylation level of Beclin1.…”
Section: Autophagy and Cancermentioning
confidence: 99%
“…Hypoacetylation of a specific set of genes results from an imbalance between KATs and HDACs and is associated with the transformed state of cancer cells (3)(4)(5)(6). HDAC inhibitors, which can suppress HDAC enzymatic activity and reactivate epigenetically silenced antitumor genes, represent useful tools for cancer prevention and therapy (7). Currently, clinical trials employing HDAC inhibitors have been hampered by their lack of specificity.…”
mentioning
confidence: 99%
“…Currently, clinical trials employing HDAC inhibitors have been hampered by their lack of specificity. Most HDAC inhibitors target a panel of HDAC superfamily members, and individual HDAC members regulate diverse cellular pathways (7,8). Therefore, the inhibition of HDAC enzymatic activity using HDAC inhibitors often results in unintentional gene activation and the development of drug resistance (9,10).…”
mentioning
confidence: 99%